1993
DOI: 10.1128/iai.61.10.4058-4063.1993
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Helicobacter pylori to gastric epithelial cells in primary cultures obtained from stomachs of various animals

Abstract: Of 35 strains of Helicobacter pyloni tested, 5 were found to adhere well to HEp-2 cells. We selected three of these adhesive strains and four from the remaining strains to examine their ability to adhere to gastric epithelial cells in primary cultures obtained by collagenase digestion of stomachs from mice, rats, Mongolian gerbils, guinea pigs, pigs, and cynomolgus monkeys. The three adhesive strains adhered well to epithelial cells from monkey and pig gastric antra. The adhesion was inhibited by incubating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Our results showed that H. pylori sonicates produced a dramatic decrease in TER in T84 monolayers and induced a rapid increase in [ 14 C]mannitol flux not only across the T84 model epithelium but also across the rat mucosa. These data suggest that the bacterium can alter the barrier function of the epithelium without adhering to it, as it is known that H. pylori does not bind to rat gastric epithelial cells (29) and that the adhesion of this bacterium to T84 cells is maximal at pH 5.4 (10), while our experiments were carried out under neutral pH conditions. Bacterial sonicates fail to produce any effect in the TER of MDCK cells (data not shown), which are also able to establish monolayers with physiological resistance.…”
Section: Discussionmentioning
confidence: 56%
“…Our results showed that H. pylori sonicates produced a dramatic decrease in TER in T84 monolayers and induced a rapid increase in [ 14 C]mannitol flux not only across the T84 model epithelium but also across the rat mucosa. These data suggest that the bacterium can alter the barrier function of the epithelium without adhering to it, as it is known that H. pylori does not bind to rat gastric epithelial cells (29) and that the adhesion of this bacterium to T84 cells is maximal at pH 5.4 (10), while our experiments were carried out under neutral pH conditions. Bacterial sonicates fail to produce any effect in the TER of MDCK cells (data not shown), which are also able to establish monolayers with physiological resistance.…”
Section: Discussionmentioning
confidence: 56%
“…Bacteria are generally most numerous in the antrum but are also found bound to patches of gastric metaplasia in the duodenum and the esophagus (5). The localized adherence of H. pylori to gastric epithelial cells as well as their apparent selectivity for the antrum (30) suggests that the organism specifically recognizes epithelial cell surface constituents. Based on hemagglutination and cell binding experiments, H. pylori was proposed to recognize 3Ј-sialyllactose (NeuAc␣2-3Gal␤1-4Glc; 3ЈSL) (13,15).…”
mentioning
confidence: 99%
“…Studies in the whole intact epithelium. Hp resides within the mucus layer or is anchored to the luminal surface by means of the adhesines (3,18,27,28). Hence, VacA toxin is presumably released by the bacterium directly onto the apical cell membrane.…”
Section: Resultsmentioning
confidence: 99%